Exploration of empathy in Cyprus nursing and health care students: A mixed method study - Karayiannis, George; Papastavrou, Evridiki; Farmakas, Antonis; Tsangari, Haritini; Noula, Maria; Roupa, Zoe (My University, 2020)
Developing professionals who are perceptive to the needs of patients and can respond by expressing empatheticbehavior is one of the aims of health care education. The aim of this study was to explore the level of empathy inhealth care students through a mixed method. The quantitative approach included the use of the Jefferson Scaleof Empathy and the qualitative a focus group approach to further deepen into the descriptive results. 869 healthcare students (RR=81%) participated in the study and the level of empathy ranged from 42 to 139 with a meanscore of 100.6 (20-140 scale). Significant statistical differences were found between the disciplines (F=8.6, p-value < 0.001) and gender (p-value < 0.001) with nursing students and women scoring the higher levels. Twofocus groups of ten participants each were conducted with 3rdand 4thyear nursing students. Four themes werederived from the analysis of these data a) empathy as an imperative component of care b) contact with theclinical reality c) the influence of family and choice of studies d) gender stereotypes. There is a lack of mixedmethodologies in the empathy research and this study provided the opportunity of a better understanding of thehealth care students’views.
Keywords: Correlation; Health; Empathy; care; Students; students; Mixed; methods